DETERMINANTS OF FACTORS AFFECTING ADAPTATION STRATEGIES TO CLIMATE CHANGE OF CASSAVA PROCESSING IN SOUTH WEST, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2023)
This study identified adaptation strategies adopted by the processors in the study area and also assessed factors affecting adaptation strategies to climate change in cassava processing in South West, Nigeria. Descriptive statistics was used to identify adaptation strategies used by cassava processors while multivariate probit model was employed to determine the factors affecting adaptation strategies engaged by farmers. Adaptation strategies adopted by processors include monitoring weather change by indigenous means, diversify into non processing activities, changing processing time, storing of produce, diversify into other processing and increasing quantity of cassava purchased the following season. Multivariate probit model identifies gender, educational level, processing experience, household size, extension contact, secondary income and marital status have statistically significant influence on climate change adaptation. This study therefore recommends improved education and awareness of climate change adaptation options in form of formal and extension education be disseminated to processors
Keywords: Climate Change Adaptation, Cassava Processing, Multivariate Probit Model, South West Nigeria